Value-added tax design and performance in Nepal: Empirical evidence on growth impact and policy prescriptions for reform - Paudel, Hari Prasad (Nepal Public Policy Review, 2025)
The study examines Value Added Tax (VAT) performance in Nepal and its impacts on economic growth using a mixed-method approach. An Auto-Regressive Distributed Lag (ARDL) model using annual time-series data (1998–2024) is employed to evaluate the VAT-growth relationship. The model uses the VAT rate, VAT share of total tax revenue, and C-efficiency ratio as key metrics of VAT design, structure, and performance. Additionally, a qualitative policy review explores VAT design, reform, and implementation challenges by incorporating insights from tax experts, academics, policymakers, and stakeholders. Findings reveal that C-efficiency ratio peaked at 61.40% in FY2018/19 and averaged 40.49% over the study period, suggesting moderate VAT performance. Furthermore, empirical results show that a 1% rise in C-efficiency and VAT revenue share increases Gross Domestic Product (GDP) per capita by 0.11% and 0.37% in the long run respectively. Conversely, a 1% rise in VAT rate decreases GDP per capita by 0.12% in the long run. These results validate that enhancing C-efficiency is more favorable to growth than raising the standard rate. Policy evaluation recommends cautiously applying a limited multi-rate VAT —reduced rates on essential goods and relatively higher rates on luxury and negative-externality goods— to lessen the tax burden on low-income groups. However, this requires prior reforms such as administrative modernization, institutional reform, development of a decentralized tax system, a digitalized system, mandatory e-invoicing, base broadening through reduced exemptions, and stronger compliance. This collective reform can increase revenue, support sustained economic growth, ensure social equity, and improve economic welfare in developing economies like Nepal.